Agricultural bio-waste of corn silk-derived porous carbon for high-performance supercapacitors. (1st December 2022) - Taslim, Rika; Halbi, Suryandri; Apriwandi, Apriwandi; Taer, Erman
Abstract: This study aims to develop a novel, simple, efficient, and low-cost method to prepare hierarchical porous carbon nanofiber derived from corn silks (CSAC) through a one-step carbonisation-physical activation process. The carbon precursors were activated by KOH solution at a high pyrolysis temperature to prepare activated porous carbon as an electrode material for supercapacitors without using binders. This study focused on the effect of different activation temperatures of 600, 700, 800, and 900 °C on the production of highly porous carbon nanofiber. An enhancement mechanism is proposed, which not only performed high nanofiber structures to possess the large specific active surface area to enhance energy density but also achieved micro-mesopore combination to realise fast ion-transport channels for boosting high power density. A maximum specific surface area of approximately 1096.95 m 2 g −1 was achieved by CSAC7. Furthermore, the electrochemical performance was evaluated using 1 M H2 SO4 solution as an electrolyte through a novel two-electrode binder-free system. The electrode materials produced a maximum specific capacitance of 237 F g −1 at a current density of 1 A g −1 . These excellent characteristics show that the synthetic approach has a great potential for fabricating high-performance supercapacitors.